Development and reliability of a kick test system for taekwondo athletes - Ribeiro, A. I. S.; Franchini, E.; Mesquita, P. H. C.; Amaral Junior, P. A.; Albuquerque, M. R. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background. the available anaerobic tests for taekwondo athletes consist of performing the maximum number of kicks in a fixed time-period. However, high-level athletes are characterized by small performance improvements. Aim. The present study aims to develop a system that can count the number of kicks, and measure the time (in milliseconds) and to test its reliability. Additionally, we examined the possibility of using video-based method as a viable alternative. Methods. The hardware system consisted of an analog accelerometer with three axes attached on the back of a kicking dummy, near the trunk region, that detected the occurrence of kicks. The sampling rate employed was 600 Hz per channel, and the resolution of the analog-to-digital converter was 10 bits for a voltage range of 0 to 3.3 Volts. The LabVIEW software was used to implement a routine with the interface of the task, as well as to process and store the collected data. Seventeen taekwondo athletes visited the laboratory on two different occasions, one week apart. Furthermore, in the first session, the performance assessment was filmed using a rate of 120 frames per second. Results. The system developed was able to identify 100% of the kicks performed by the athletes, and demonstrated good absolute and relative reliability, and the video-based analysis can be used as a more viable tool to coaches and physical and conditioning professionals. Conclusions. Our kick test system can be considered a reliable specific test for the assessment of high-intensity interval taekwondo-specific performance.